PENGARUH LIVE STREAMING DAN ONLINE CUSTOMER REVIEW TERHADAP PURCHASE INTENTION PADA GENERASI Z PENGGUNA TIKTOK SHOP DI KOTA PEMATANGSIANTAR - Octavia Selpi Sihotang; Benjamin Albert Simamora; Anggun Tiur Ida Sinaga (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effect of live streaming and online customer reviews on purchase intention among Generation Z users of TikTok Shop in Pematangsiantar. This research employs a quantitative approach. The population of this study consists of Generation Z users of TikTok Shop in Pematangsiantar City. The sample comprises 398 respondents, selected using incidental sampling technique. The research instrument was tested using validity and reliability tests, with reliability measured by Cronbach’s Alpha. Data analysis was conducted using IBM SPSS Statistics, including classical assumption tests such as normality, multicollinearity, and heteroscedasticity tests, as well as multiple linear regression analysis, t-test (partial), F-test (simultaneous), and coefficient of determination (R²). The results indicate that live streaming has a positive and significant effect on purchase intention, as evidenced by the t-test result where t-value (15.485) > t-table (1.966) with a significance value of 0.000 < 0.05. Online customer reviews also have a positive and significant effect on purchase intention, with a t-value of 8.129 > t-table of 1.966 and a significance value of 0.000 < 0.05. Simultaneously, live streaming and online customer reviews significantly influence purchase intention, as indicated by the F-test result where F-value (340.357) > F-table (3.02) with a significance value of 0.000 < 0.05. The coefficient of determination (R²) is 0.633, indicating that 63.3% of purchase intention is explained by these variables, while the remaining is influenced by other factors outside this study.The conclusion of this study shows that live streaming has a more dominant influence than online customer reviewsin increasing purchase intention.